Effect of Roasting on the Proximate Composition, Antioxidant Activity, and Functional Properties of Afrostyrax lepidophyllus (Country Onion) Seeds - Wiyeh Claudette Bakisu Muala; Tonfack Djikeng Fabrice; Noumo Ngangmou Thierry; Ngangoum Eric Serge (Journal of Food Quality)
Afrostyrax lepidophyllus seed is a nontimber forest product which has a strongly ferocious smell of garlic or onion. It is widely used in central and west Africa in traditional medicine and as spices. The seeds used as spices are generally roasted in order to improve their flavor or aroma. However, roasting conditions vary and also affect the quality of the final product. In order to define the best roasting conditions, A. lepidophyllus seeds were roasted using microwave (200, 300, and 450 W for 10 min), oven (10 and 20 min at 180°C), and pot (5, 10 and 15 min) and blended into flour. The proximate composition, physical, functional, and antioxidant activities of (control) and roasted flours were analyzed. Irrespective of the roasting method, there was a significant increase in fiber content (oven (0.5–1.20%), pot (0.47–1.27%), and microwave (0.50–0.93%)) with increase in time and temperature. The carbohydrate content increased (77.74–81.50%), while protein content dropped with roasting. A significant increase in ash, total phenolic contents (TPC), antioxidant activity (AOA), and functional properties compared to the control was recorded. Roasting A. lepidophyllus seeds in the pot at 250 ± 5°C, 15 min was found to be a good method which maintained or increased its functional and physicochemical properties. With the good TPC and AOA, A. lepidophyllus roasted flour can be a potential ingredient for nutraceutical food development.